Numerical studies of silica precipitation/dissolution - Lai, C.H.; Bodvarsson, G.S.; Witherspoon, P.A. (Lawrence Berkeley Laboratory, 1985)
In this paper we describe our numerical simulator PIC (pressure-temperature-chemistry), and also present the methods we use to reduce error due to numerical diffusion. Examples of the application of this approach to two problems are included. The first problem involves non-isothermal flow of supersaturated silica through single fractures. The precipitation of silica in the fractures is modeled and the resulting permeability and flow rate decreases are calculated. The second problem involves field data collected at the Ellidaar geothermal field in Iceland. After 15 years of fluid production, significant declines in pressure and temperature have been observed along with changes in silica concentrations. In order to illustrate the applicability of our model to such data, we have developed a simple numerical model that fits well with the observed production history. The applicability of our coupled method of analyzing the changing reservoir conditions is demonstrated, and the result is a more detailed understanding of the geothermal system.